Socialization and Demonstration of Seaweed Biscuit Production in an Effort to Reduce Stunting Rates in Pulau Persatuan Village, Pulau Sembilan District, Sinjai Regency - Debi, Hesli; Azis, Abdul; Salim, Iqbal (Journal of Mestika Nusantara Satu Community Services, 2024)
Stunting is a significant public health issue that affects millions of children worldwide. The effects of stunting are not limited to physical growth deficits; they also encompass cognitive and developmental challenges that can have long-term implications throughout a child's life. Therefore, the issue of stunting needs serious and sustainable attention and handling. Desa Pulau Persatuan is one of the villages in the Pulau Sembilan District of Sinjai Regency with a relatively high number of stunting cases and has received attention from the Sinjai Regency local government. On one hand, Desa Pulau Persatuan is a producer of seaweed in Sinjai Regency, thus having resource potential that can be utilized to help address stunting. Therefore, a community service activity was conducted in the form of socialization and demonstration of seaweed biscuit production with the aim of helping to reduce the number of stunting cases in Pulau Persatuan village through the fulfillment of nutrition for children and pregnant mothers. The activity was conducted in the form of socialization and direct demonstration to the community at the Pulau Persatuan Village Office, Pulau Sembilan District, followed by product packaging and concluded with the handover of the product to the head of Pulau Persatuan Village. The activity was carried out smoothly and attended by 14 participants who showed high enthusiasm during the demonstration and discussion, and liked the produced biscuits.